Kewenangan Komisi Yudisial (Studi Perbandingan Komisi Yudisial Republik Indonesia dan Consiglio Superiore Della Magistratura, Italia) - Farid Nur Isjayanto; Nurimansyah Setivia Bakti (Bahasa Indonesia, 2025)
This study examines the comparison of authority between the Judicial Commission of the Republic of Indonesia (KY) and the Consiglio Superiore della Magistratura (CSM) of Italy in maintaining judicial independence and accountability. KY is primarily responsible for overseeing the ethics and conduct of judges and proposing the appointment of Supreme Court justices. However, its authority is limited, as the final decision regarding disciplinary sanctions against judges remains with the Supreme Court. In contrast, the CSM of Italy holds broader powers, including the appointment, promotion, transfer, and disciplinary actions of judges, making it more effective in ensuring an independent and accountable judiciary. This study employs normative legal research with a comparative approach, analyzing primary data in the form of legislation and court decisions, as well as secondary data from legal literature and journals. The findings indicate that the CSM system is more effective in safeguarding judicial independence and accountability than KY Indonesia. Therefore, Indonesia can learn from the CSM's practices to strengthen KY's role and authority in enhancing the integrity and independence of the judiciary in Indonesia.